Argia koroivarum sp. nov. (Odonata: Coenagrionidae) from Minas Gerais state, Southeastern Brazil. - Vilela, Diogo Silva [UNESP]; Guillermo-Ferreira, Rhainer; Koroiva, Ricardo (Magnolia Press, 2023)
Argia koroivarum sp. nov. (BRAZIL, Minas Gerais state, São Roque de Minas, Parque Nacional Serra da Canastra, 9.iv.2019, (-20.2323, -46.6084, 1306m asl), D.S. Vilela, R. Guillermo, R. Koroiva leg., Laboratory of Ecological Studies on Ethology and Evolution (LESTES), Uberaba, Minas Gerais State, Brazil) is described, illustrated, and diagnosed based on specimens collected in Minas Gerais state, Brazil. The new species can be diagnosed from its congeners by the morphology of male ligula, dorsal branch of paraproct, and of female mesostigmal lobes.